Upaya Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Pancasila melalui Metode Team Game Tournament (TGT) pada Siswa Kelas V SD Negeri 064966 Medan - Fitri, Aulia; Sari, Suci Perwita; Pakpahan, Lindang Marturasi (ALSYS, 2025)
This study is motivated by the low student activity and learning outcomes in the subject of Pancasila Education among fifth-grade students at SD Negeri 064966 Medan, evidenced by minimal student participation and failure to meet the Minimum Competency Criteria (KKM). The objectives of the study are to (1) improve student learning activity and (2) enhance student learning outcomes in Pancasila Education. The research employed Classroom Action Research (CAR) over two cycles, involving the stages of planning, implementation, observation, and reflection. Data were collected through observations of student activity, learning outcome tests, and documentation. Learning mastery increased from 21.60% of students meeting the criteria in the pre-cycle to 62.10% in cycle I, and further to 86.50% in cycle II. Observations of student learning activity also showed improvement, with average group scores progressively increasing from cycle I to cycle II. The implementation of the Team Game Tournament (TGT) method proved effective in actively engaging students in learning and promoting more optimal learning outcomes. In conclusion, the TGT method can be applied as a teaching strategy to support the enhancement of student activity and learning outcomes in Pancasila Education.